Sulfur (³⁴S/³²S) isotope composition of gypsum and implications for deep cave formation on the Nullarbor Plain, Australia - Lipar, M.; Ferk, M.; Lojen, S.; Barham, Milo (Società Speleologica Italiana, 2019)
Large deep caves with little relation to surface topography are distinctive karst features on the Nullarbor Plain of Australia. The presence of gypsum deposits and chemoautotrophic bacteria within the caves have been suggested as evidence for cave formation and (or) enlargement via sulfuric acid speleogenesis. To test this hypothesis, the stable sulfur isotope compositions (δ34S) of both cave gypsum and surface gypsum were measured. Analyses yielded relatively high, positive δ34S values from both cave gypsum and surface gypsum, arguing against gypsum genesis via microbial chemoautotrophy, and more broadly, sulfuric acid speleogenesis. Instead, the gypsum is interpreted as forming via evaporation of seawater during the Quaternary.